Attachment Insecurity in Rats Subjected to Maternal Separation and Early Weaning: Sex Differences - Zeng, Haiyan; Yu, Zijia; Huang, Qingjun; Xu, Haiyun (Frontiers in Behavioral Neuroscience, 2021)
Attachment insecurity in the forms of attachment anxiety and avoidance is associated with mental disorders in humans. In this research field, rodents, especially mice and rats, are commonly used to study social behaviors and underlying biological mechanisms due to their pronounced sociability. However, quantitative assessment of attachment security/insecurity in rodents has been a major challenge. The present study identified attachment insecurity behaviors in rats subjected to maternal separation (MS) during postnatal days (PD) 2-16 and early weaning (EW) during PD17-21. This MSEW procedure has been used to mimic early life neglect in humans. After MSEW, rats continued to survive until early adulthood when they were subjected to open-field, social interaction, and elevated-plus maze tests. Compared to CNT rats in either gender, MSEW rats moved longer distances at higher velocities in the open-field. The MSEW rats also showed lower ratios of travel distance at central zone over that on whole arena of the open-field compared to CNT rats. In social interaction test, male CNT rats preferred to investigate an empty cage than females; whereas female CNT rats spent more time with a partner-containing cage as compared to males. This gender-specific difference was reversed in MSEW rats. On elevated-plus maze female CNT rats exhibited more risk-taking behaviors as compared to male counterparts. Moreover, female MSEW rats experienced a greater difficulty in making a decision on whether approaching to or averting from which arms of elevated-plus maze. Taken together, male MSEW rats behaved like attachment anxiety while females’ phenotype is alike to attachment avoidance described in humans. These results shall prompt further application of MSEW rat in abnormal psychology and biological psychiatry research.